Separate and combined effects of famine exposure and menarche age on metabolic syndrome among the elderly: a cross-sectional study in China - Congzhi Wang; Jiazhi Wang; Rui Wan; Ting Yuan; Liu Yang; Dongmei Zhang; Xiaoping Li; Haiyang Liu; Lin Zhang (BMC Women's Health, 2023)
Abstract Background Epidemiological studies have revealed multiple risk factors for metabolic syndrome. However, there are no consistent findings on the association between famine exposure, age at menarche, and the prevalence of metabolic syndrome. This cross-sectional study aimed to reveal the individual and combined effects of famine exposure and age at menarche on the prevalence of metabolic syndrome among elderly women. Methods Four thousand seven hundred seventy participants between 60 and 93 years of age were selected from the China Health and Retirement Longitudinal Study. Statistical differences between the baseline characteristics of famine exposure, age at menarche, and metabolic syndrome were evaluated using the t-test, F-test, and Chi-square test. Three multivariable-adjusted logistic regression models were used to test the association between famine exposure, age of menarche, and the odds ratio of metabolic syndrome. Results Two thousand one hundred ninety-eight (46.08%) participants had metabolic syndrome, while 2572 (53.92%) participants did not. Furthermore, 3068 (64.32%) women reported onset of menarche under 15 years of age, while 1702 (35.68%) women reported onset of menarche above 16 years of age. Regarding the separate association of famine exposure and age of menarche with metabolic syndrome, in model three, the adolescence/adulthood famine exposure group vs. no famine exposure group odds ratio was 2.45 (95% CI 2.02, 2.97), and the older than 16 years vs. younger than 15 years group odds ratio was 1.23 (95% CI 1.09, 1.39), which was the highest odds ratio among the three models. Regarding the combined association of famine exposure and age of menarche with metabolic syndrome, in model three, among the age of menarche ≤ 15 years group, the adolescence/adulthood famine exposure vs. no famine exposure group odds ratio was 2.45 (95% CI: 1.91, 3.14); among the menarche age ≥ 16 years group, the adolescence/adulthood famine exposure stages vs. exposed group odds ratio was 3.27 (95% CI: 2.44, 4.38), which was the highest odds ratio among the three models. Conclusion These findings suggested that famine exposure and age at menarche, either separately or in combination, were positively associated with the prevalence of metabolic syndrome among older women.